Representation of Gender Equality in Downy's Product Advertising: A Semiotic Analysis of Roland Barthes - Putu Anggi Amalia; Abdul Fadli Kalaloi (Budapest International Research and Critics University, 2022)
The purpose of this study was to semiotically analyze the representation of gender equality in Downy's product advertisements. This research uses qualitative research with constructivist paradigm approach. The researcher determines that the object of this research is the advertisement itself, namely the Downy version of the 'Together with Downy Harumkan Namamu for Free Expression' version. Based on the results of the analysis, it can be concluded that this advertisement displays a clear meaning where this advertisement mentions many stereotypes of prohibitions or limitations that exist in society against women, this advertisement also mentions that these stereotypes are not always true as long as it is beneficial for themselves and many people. In addition, this reaffirms that a woman really needs to get equality, with the expressions shown in the advertisement convincing that women are also capable and have high enthusiasm to do anything they want. Furthermore, this advertisement wants to show the myth that is interpreted about the stereotypes that exist in society where women have many limitations such as in expression, in career, and in leading.